Colloquial Arabic (Levantine) the complete course for beginners - McLoughlin, Leslie; Routledge (Firm) (Boca Raton, FL: Routledge, 2009)
Features lots of exercises to help perfect the pronounciation and listening skills especially for the beginners
Title from container
Keywords: Arabic language; Arabic language -- Grammar; Arabic language -- Study and teaching